Vibrational Analysis Over An Aircraft Wing Section - Vasthadu Vasu Kannah, Ajin Branesh A, Pon Maa Kishan, Aishwarya Dhara (International Journal of Advanced Science and Technology, 2020)
This paper is a predominant work that deals with the structural analysis on a passenger aircraft wing when it is subjected to vibration.During flight conditions at high speed this wing of an aircraft is subjected to maximum lift forces over the top surface of the wing which will pave way for an increase in g-force and it starts to vibrate. This is a major factor that resist or reduces the stability of an aircraft.For various analysis the maximum lift distribution over a wing for both lift force and acceleration are considered in this work. The FEA results are then compared with the reference model.